Catalytic Cracking of Methyl Ester from Used Cooking Oil with Ni-Ion-Exchanged ZSM-5 Catalyst - Alfernando, Oki; Sarip, Rozie; Anggraini, Titin; Nazarudin, Nazarudin (UI Scholars Hub, 2019)
Fossil crude reserves continue to decline, eventually leading to a reduced availability of fuel oil in Indonesia. Thus, the use of alternative plant-derived renewable energy sources, such as biodiesel should be considered. However, biodiesel as a fuel alternative has many drawbacks. In this study, biodiesel was cracked using a Ni-ZSM-5 catalyst to improve its quality. This work aimed to synthesize and characterize the Ni-ZSM-5 catalyst obtained from ion-exchange and catalytically crack methyl esters from used cooking oil. Three Ni-metal concentrations (1%, 2%, and 3%) were used for the ion-exchange of ZSM-5. Ni catalysts were then utilized for catalytic cracking at three temperatures (450 ºC, 500 ºC, and 550 ºC). X-ray diffraction and scanning electron microscopy (SEM) analysis showed that the catalyst was in an aggregate form. SEM-energy-dispersive X-ray spectroscopy analysis indicated that Ni was successfully adsorbed by the catalyst. The gravimetry of the catalytically cracked product revealed that the highest oil fraction was obtained using 1% Ni catalyst at 450 ºC. The largest chain obtained with this catalyst was diesel oil (C13-C19) with total 92.96% of covered peak area in the chromatogram/component quantity from gas chromatography.